Handcuffing in India: Constitutional restraints, judicial activism, and human rights perspectives (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Handcuffing of arrested persons and undertrial prisoners has remained a contentious issue within the Indian criminal justice system. Although often justified by law enforcement agencies on grounds of security and prevention of escape, indiscriminate handcuffing undermines the constitutional guarantees of personal liberty, equality, and human dignity. The Supreme Court of India has consistently held that handcuffing is an exceptional measure and not a routine practice. This article undertakes a comprehensive doctrinal analysis of the legal framework governing handcuffing in India, examining constitutional provisions, statutory mandates, and landmark judicial pronouncements. It further situates the Indian position within the broader context of international human rights law. The study concludes that despite robust judicial safeguards, the persistence of routine handcuffing reflects structural and attitudinal deficiencies in law enforcement, necessitating systemic reforms and enhanced accountability mechanisms.